Electrolyte Mixtures Based on Ethylene Carbonate and Dimethyl Sulfone for Li‐Ion Batteries with Improved Safety Characteristics. Issue 11 (7th May 2015) - Hofmann, Andreas; Migeot, Matthias; Thißen, Eva; Schulz, Michael; Heinzmann, Ralf; Indris, Sylvio; Bergfeldt, Thomas; Lei, Boxia; Ziebert, Carlos; Hanemann, Thomas
Abstract: In this study, novel electrolyte mixtures for Li‐ion cells are presented with highly improved safety features. The electrolyte formulations are composed of ethylene carbonate/dimethyl sulfone (80:20 wt/wt) as the solvent mixture and LiBF4, lithium bis(trifluoromethanesulfonyl)azanide, and lithium bis(oxalato)borate as the conducting salts. Initially, the electrolytes are characterized with regard to their physical properties, their lithium transport properties, and their electrochemical stability. The key advantages of the electrolytes are high flash points of >140 °C, which enhance significantly the intrinsic safety of Li‐ion cells containing these electrolytes. This has been quantified by measurements in an accelerating rate calorimeter. By using the newly developed electrolytes, which are liquid down to T =−10 °C, it is possible to achieve C ‐rates of up to 1.5 C with >80 % of the initial specific capacity. During 100 cycles in cell tests (graphite||LiNi1/3 Co1/3 Mn1/3 O2 ), it is proven that the retention of the specific capacity is >98 % of the third discharge cycle with dependence on the conducting salt. The best electrolyte mixture yields a capacity retention of >96 % after 200 cycles in coin cells. Abstract : Safer solvents: A novel solvent mixture for Li‐ion batteries is developed based on ethylene carbonate and dimethyl sulfone. The system shows significantly improved safety characteristics, yet maintains accurate cell performance and excellent long‐term stability. The mixture may be interesting for other applications too, such as supercapacitors or other Li‐based technologies.